The Business of Being Barbie. A Case Study of an Ambidextrous Intellectual Property Protection Strategy - Jankowska, Marlena; Romanello Bueno , José Geraldo (PRAWO i WIĘŹ, 2026)
This paper examines Mattel’s intellectual property strategy for Barbie through a dual SWOT framework, demonstrating how the brand operates simultaneously as both a defensive fortress and an offensive growth engine. Drawing on legal records, financial disclosures and market data, the study demonstrates that Barbie’s intellectual property portfolio exemplifies an “ambidextrous strategy” – one that protects brand integrity through rigorous enforcement while expanding across film, fashion, gaming and digital ecosystems through strategic licensing and partnerships. The weighted SWOT analysis shows that Barbie’s defensive strengths significantly outweigh external threats, thereby creating a formidable enforcement infrastructure capable of countering counterfeiters, AI-driven look-alikes and jurisdictional challenges. On the offensive side, Barbie’s monetization capabilities align closely with expansion opportunities, enabling the brand to scale into new markets while managing exposure risks through curated growth. These parallel strategies are not mutually exclusive but symbiotic: enforcement actions against counterfeiters preserve consumer trust, which in turn enables luxury collaborations, while trade dress protection enhances the appeal of IP extensions such as feature films and video games. The paper contributes to intellectual property scholar ship by demonstrating that SWOT analysis can serve as a practical framework for shaping and assessing IP strategy and to business strategy literature by illustrating how established brands maintain market dominance through calibrated, complementary defensive and offensive IP management in competitive, fast-changing industries.